Estimation of Parameters of Inflated Poisson-Lindley Distribution for Adult Out-migration - Singh, Brijesh P.; Singh, Naraj K.; Dixit, Shweta (Journal of Institute of Science and Technology, 2015)
The aim of this paper is to study the distribution of adult migrants from the household. The inflated Poisson-Lindley distribution is found to be a suitable model to describe this distribution. The parameters of this distribution have been estimated by two methods and suitability of model is checked by using real data sets. Findings may help planners and policy makers for designing more effective and reasonable policies. Journal of Institute of Science and Technology, 2015, 20(2): 6-10